PERUBAHAN MATA PENCAHARIAN DAN PROSES ADAPTASI SOSIAL EKONOMI KELUARGA TERKENA DAMPAK PHK PANDEMI COVID 19 - Larasati, Erika (JOURNAL OF SOCIAL, JUSTICE AND POLICY, 2022)
The Covid pandemic that has hit the world has caused Indonesia's economy to slump, employment opportunities have become increasingly difficult. Many companies have cut off working relationships with their employees, one of which is Kualanamu International Airport (KNIA). This type of research uses a qualitative approach which aims to examine the socioeconomic conditions of the families of the Kualanamu Airport layoff victims in Sidodadi Ramunia Village for the changes in their livelihoods and what strategies they have adopted. The number of informants in this study were 3 main informants, namely the victims of layoffs at Kualanamu Airport by using purposive sampling technique. Data collection methods were collected through direct field observations, interviews, literature studies, and documentation, until finally conclusions can be drawn from the results of the research. The results showed that the socio-economic conditions of the layoff victims were low because it was seen from the socio-economic indicators which included income, health, education, clothing & food, housing and social interaction that were still far from feasible. Due to changes in livelihoods due to layoffs experienced by key informants, it resulted in a decline in the socio-economic situation so that they could adapt. And based on the strategy they did they succeeded in improving their socio-economic which had declined.